Daniel A. González Madrid y Manuel Ortiz Heras (coords.), El Estado del bienestar entre el franquismo y la Transición, Madrid, Sílex, 2020, 387 páginas - Cazorla, Antonio (Hispania Nova, 2021)
Book review